Understanding geographical variations in health system performance: a population-based study on preventable childhood hospitalisations. Issue 6 (1st June 2022) - Silwal, Pushkar Raj; Exeter, Daniel; Tenbensel, Tim; Lee, Arier
Abstract : Objective: To investigate interdistrict variations in childhood ambulatory sensitive hospitalisation (ASH) over the years. Design: Observational population-based study over 2008–2018 using the Primary Health Organisation Enrolment Collection (PHO) and the National Minimum Dataset hospital events databases. Setting: New Zealand primary and secondary care. Participants: All children aged 0–4 years enrolled in the PHO Enrolment Collection from 2008 to 2018. Main outcome measure: ASH. Results: Only 1.4% of the variability in the risk of having childhood ASH (intracluster correlation coefficient=0.014) is explained at the level of District Health Board (DHB), with the median OR of 1.23. No consistent time trend was observed for the adjusted childhood ASH at the national level, but the DHBs demonstrated different trajectories over the years. Ethnicity (being a Pacific child) followed by deprivation demonstrated stronger relationships with childhood ASH than the geography and the health system input variables. Conclusion: The variation in childhood ASH is explained only minimal at the DHB level. The sociodemographic variables also only partly explained the variations. Unlike the general ASH measure, the childhood ASH used in this analysis provides insights into the acute conditions sensitive to primary care services. However, further information would be required to conclude this as the DHB-level performance variations.